Regulations, brokers, and interlinkages: The institutional organization of wholesale markets in India - Bart Minten; Anneleen Vandeplas; Johan F. M. Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2011)
There is a vigorous debate on the liberalization of heavily regulated agricultural markets in India. A crucial institutional characteristic is the role of state regulated brokers in wholesale markets. Relying on data from a unique survey in Uttarakhand, a state in North-India, we find that regulations on margins are ineffective as most brokers charge rates that significantly exceed the regulated ones. We also find that a majority of firmers self-select into long-tfirm relationships with brokers. These relationships allow some of the firmers to interlink credit and insurance markets to the agricultural output market. This interlinkage does however not appear to be an instrument for firmer exploitation (as it does not lead to worse inputs, high interest rates, or lower implicit output prices), but is seemingly an extra service by brokers as to establish firmer loyalty to him and thus to ensure future supplies.
Keywords: Q12; Q13; L15; 330; India; agricultural marketing; brokers; interlinkages